A prevalence survey of patients with indwelling urinary catheters on district nursing caseloads in the United Kingdom: The Community Urinary Catheter Management (CCaMa) Study. Issue 4 (July 2020) - Prieto, Jacqui; Wilson, Jennie; Bak, Aggie; Denton, Andrea; Flores, Ashley; Lusardi, Gail; Reid, Matthew; Shepherd, Lesley; Whittome, Niamh; Loveday, Heather
Background: Catheter-associated urinary tract infection (CAUTI) is common in both hospitals and the community. Aim: To investigate the prevalence of indwelling urinary catheters on district nursing caseloads in the UK. Methods: Participants were recruited through the Infection Prevention Society (IPS). An electronic survey was undertaken on a single day between November 2017 and January 2018. Data were analysed using descriptive statistics. Findings: A total of 49, 575 patients were included in the survey, of whom 5352 had an indwelling urinary catheter. This gave a point prevalence of 10.8% (95% confidence interval [CI] = 10.53–11.07), which varied between organisations, ranging from 2.36% (95% CI = 2.05–2.73) to 22.02% (95% CI = 20.12–24.05). Of catheters, 5% were newly placed (within four weeks). Of these, most (77%) had a documented indication for insertion. Only half of patients with a newly placed catheter had a plan for its removal. This varied between organisations in the range of 20%–96%. Only 13% of patients had a patient-held management plan or 'catheter passport' but these patients were significantly more likely to also have an active removal plan (28/36 [78%] vs. 106/231 [46%]; P < 0.0001). Alternative bladder management strategies had been considered for 70/267 (26%) patients. Discussion: The management of patients with an indwelling urinary catheter represents a significant component of district nursing caseloads. Given the high proportion of newly catheterised patients without an active management plan for removal of the catheter, the establishment of an optimal management pathway should be the focus of future prevention efforts.